Treatment of Pediatric Condylar Fractures: A 20-Year Experience. Issue 6 (December 2015) - Ghasemzadeh, Ali; Mundinger, Gerhard S.; Swanson, Edward W.; Utria, Alan F.; Dorafshar, Amir H.
Abstract : Background: The purpose of this study was to define patterns of injury and treatment for condylar and subcondylar fractures and evaluate short-term outcomes in the pediatric population. Methods: A retrospective chart review was performed on pediatric patients with mandibular condylar fractures who presented between 1990 and 2010. Computed tomographic imaging was reviewed for all patients to assess fracture characteristics. Mandibular fractures were codified using the Strasbourg Osteosynthesis Research Group and Lindahl classification methods. Results: Sixty-four patients with 92 condylar fractures were identified. Of these patients, 29 had isolated condylar fracture and 35 had a condylar fracture associated with an additional mandibular arch fracture. The most common fracture patterns were diacapitular fracture in the Strasbourg Osteosynthesis Research Group system ( n = 46) and vertical condylar head fracture in the Lindahl system ( n = 14). Condylar fracture with additional mandibular arch fractures were treated with maxillomandibular fixation more often than patients with condylar fracture [ n = 40 (74.1 percent) versus n = 14 (25.9 percent); p = 0.004]. No condylar fracture was treated in an open fashion. Forty-three patients returned for follow-up. The median follow-up period was 81 days (interquartile range, 35 to 294 days). Ten patients had complications (23.3 percent). The most common complication was malocclusion ( n = 5). Nine of 10 patients with complications had condylar fracture with an additional mandibular arch fracture. Conclusions: Closed treatment of condylar fractures yields satisfactory results in pediatric patients. Pediatric patients with condylar fractures combined with additional arch fractures experience a higher rate of unfavorable outcomes. Abstract : Coding Perspective for this Article is on Page 1287.